STUDENTS’ PERCEPTION ON LEARNING HEUTAGOGY IN THE ENGLISH FOR YOUNG LEARNER - Ekawati, Anita Dewi; Lustyantie, Ninuk; Chaeruman, Uwes Anis (IJLECR (International Journal of Language Education and Cultural Review), 2022)
To attract the attention of students as learners, teachers should use an approach that is in accordance with the characteristics of students. Students as generation z or digital natives, have a great interest in the digital world. Therefore, the process of learning and teaching can get out of the traditional zone by using the heutagogy method. This heutagogy method is applied to students who take English for Young learners. The results obtained from 85 students’ answers to the questionnaire about students’ perceptions of learning using heutagogy showed positive results. Students respond well to heutagogy learning. Heutagogy is expected to be a teaching choice for students later.